Optimizing Imaging of Three-Dimensional Multicellular Tumor Spheroids with Fluorescent Reporter Proteins Using Confocal Microscopy - Lucia le Roux; Andrei Volgin; David Maxwell; Katashi Ishihara; Juri Gelovani; Dawid Schellingerhout (Molecular Imaging)
Tumor spheroids more faithfully mimic tumor biology than monolayer cultures and require three-dimensional microscopy. Our goal in this study was to overcome the limitations of signal to noise ratio that have traditionally limited three-dimensional imaging to depths of 100 μm or less. We studied the expression of hypoxia-inducible factor 1α (HIF-1α), the main regulator of cellular hypoxic response in C6 glioma spheroids. In our spheroids, red fluorescent protein is expressed constitutively and green fluorescent protein is expressed conditionally under control of a HIF-1α promoter. In this article, we show a series of optimizations that allowed us to obtain excellent quality confocal microscopy images at imaging depths of up to 320 μm. The combined use of special objectives, glass-bottomed culture dishes, and depth-dependent laser output modulation extended our depth range beyond previously accepted limits. This allowed us to image up to the equator of spheroids of 650 μm diameter, allowing interrogation of HIF-1α expression from the spheroid periphery to its hypoxic center.